A Fragmented Transformation: Giovanni Pirelli's War Writings, 1940–1944. Issue 3 (12th August 2016) - Love, Rachel E.
Abstract : In this paper, I examine the unpublished First World War diaries of Giovanni Pirelli – heir to the helm of the Pirelli tyre company – for their account of how the war and fall of Fascism may have catalysed his dissociation from his family, his class, and his ideological foundation. In the post-war period, Pirelli traced the source of his rejection of his inheritance to his experiences during the Russian retreat, but in the moment, the expression of this kind of transformation is fragmentary and complex. Scholars often look to war diaries and letters for their testimony to the state of the individual in combat. Through close reading, I trace how Pirelli's writings negotiate his immense privilege and his attempt to construct a moral identity in the midst of war. I consider how they demonstrate his break with his wartime ideals and Fascism and how they anticipate his later transition from industrial heir to socialist activist. My examination of these diaries reveals the ambiguities inherent in this transformation of Fascist and bourgeois subjectivity. Italian summary: Quest'articolo esamina i diari di guerra di Giovanni Pirelli – primo erede dell'azienda Pirelli e noto intellettuale socialista e anticolonialista del dopoguerra – per come raccontano la sua esperienza della seconda guerra mondiale, la fine del fascismo e la Resistenza, e per come anticipano il suo distacco dalla sua famiglia, la sua classe, e le sue origini ideologiche. Negli anni del dopoguerra, Pirelli ha ritenuto la ritirata dalla Russia come l'evento alla base di questo suo gran rifiuto, ma durante il conflitto l'espressione di queste trasformazioni è più frammentaria e complessa. Questo articolo ripercorre il modo in cui i diari articolano la sua consapevolezza dei privilegi familiari e sociali, e il suo sforzo di costruire una sua personale identità morale. Un'esame di questi scritti offre un suggestivo ritratto delle ambiguità del processo di trasformazione di un soggetto fascista e borghese. Questo studio è contestualizzato nel quadro più ampio degli studi su lettere e diari di guerra e la loro testimonianza sullo stato dell'individuo in combattimento.